An Analysis of EFL Students Motivation in Post Pandemic Era at MAN 2 Kota Padang - Yesi April Dayani; Devi Kurnia Alamsyah (Journal of English Language Teaching, 2023)
Motivation is very important and affects students' ability to learn English. This study aims to find out how students' motivation in learning English after the pandemic and what motivates students’ to learn English after the pandemic. In this case, students’ are encouraged to express their feelings. This research used a quantitative descriptive approach. In this research, the researcher focus on 72 students’ from MAN 2 Kota Padang. This study used observation and questionnaires. Based on data analysis, it was found that students’ motivation after the pandemic increased. This is concluded from 2 indicators of motivation that have been observed. The percentage of each aspect is high. After the pandemic, students are pleased with their English learning experience and more motivated to learn the English language after pandemic.